2021
DOI: 10.13057/biodiv/d220661
|View full text |Cite
|
Sign up to set email alerts
|

A case study of agroforestry practices and challenges in Mt. Merapi risk and hazard prone area of Indonesia

Abstract: Abstract. Rozaki Z, Rahmawati N, Wijaya O, Mubarok AF, Senge M, Kamarudin MF. 2021. A case study of agroforestry practices and challenges in Mt. Merapi risk and hazard-prone area of Indonesia. Biodiversitas 22: 2511-2518. This paper presents a case study of agroforestry (AF) practices and challenges in Mt. Merapi risk and hazard-prone area of Indonesia. AF has been practiced by farmers in Mt. Merapi risk and hazard-prone area from older generation. Each area in Mt. Merapi has different types of AF such as agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Merapi, people livelihood is dominated by farmers and sand miners, respectively (Bachri et al 2015). Rozaki et al (2021) showed that AF has been practiced by many people in Mt.…”
Section: Introductionmentioning
confidence: 99%
“…Merapi, people livelihood is dominated by farmers and sand miners, respectively (Bachri et al 2015). Rozaki et al (2021) showed that AF has been practiced by many people in Mt.…”
Section: Introductionmentioning
confidence: 99%
“…• Smallholder agroforestry has over 10 years of experience [165]; • Traditional agroforestry practices [166], silviculture practices [65], and soil and water conservation technologies are available to smallholders [167,168].…”
Section: Strength (S)mentioning
confidence: 99%
“…• A lack of awareness regarding the positive influence of proper silvicultural management and limited technical capacity [182]; • Agroforestry is regarded as the second livelihood for some farmers [18,165]; • Some farmers do not fertilize trees or only do so during the intensive maintenance of crops [165]. Kebun campuran (mixed garden) is not intensively managed [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Merapi. Rozaki et al (2021b), through their study in Mt. Merapi, found that AF practices vary depending on the purpose of the farmers, such as some farmers are practicing AF for economic purposes.…”
Section: Factors Affecting the Perceptionmentioning
confidence: 99%